Comparison of pharmacodynamic properties of three different aspirin formualtions in the patients with stable coronary disease - Antić, Ana; Stanojković, Zoran; Vučić, Miodrag; Lazarević, Milan; Vacić, Nebojša (Vojnosanitetski pregled, 2021)
Background/Aim. The platelet aggregation, as a laboratory test for assessment of platelet function, is very efficient for optimal antiplatelet treatment and also to identify individuals who have suboptimal response to antiplatelet drugs, such as aspirin and clopidogrel. The aim of this study was to determine the level of inhibition of platelet aggregation using impedance aggregometry in the patients receiving different preparations of acetylsalicylic acid (ASA) in a dose of 100 mg per day. Methods. The examination included 215 patients (110 men and 105 women), treated with one of three different ASA preparations after acute myocardial infarction, as a single therapy or with clopidogrel. Among them, 89 patients were on Aspirin protect® (Bayer, Germany) – Group 1 and 66 patients were on Cardiopirin® (GL Pharma GMBH, Austria) – Group 2, while 60 patients were taking Andol® (Pliva, Croatia) – Group 3. The groups were equal in the presence of factors that can influence platelet aggregation (age, gender, smoking, diabetes, taking other drugs). The platelet function was measured using the impedance aggregometer Multiplate (Multiplate Platelet Function Analyzer, Roche) in the blood samples with heparin for the platelet aggregation activated by the arachidonic acid (ASPI) and by thrombin (TRAP) tests [the area under the aggregation curve (AUC) was used to express the aggregation response over the measured time (AU*min)]. Results. Efficacy of ASA preparations showed statistically significant differences among the three investigated groups (χKW2 = 46.279; p
Keywords: platelet aggregation; aggregation inhibitors; aspirin; clopidogrel; acute coronary syndrome; treatment outcome.